BEVERAGE STORE BUSINESS LICENSE REGULATION - Tantri, Novia Ayu (Communale Journal, 2023)
This study was conducted to understand the arrangement and licensing mechanism for taverns from a legal perspective. Licensing regulations before the Job Creation Law, especially the licensing process in the regions, could have been more friendly to the business sector. The presence of the Job Creation Law, which changed several articles of the Licensing Law, greatly affected the ease of business licensing. This study uses normative juridical research methods with statutory, conceptual, and historical approaches. The results of this study indicate that the tavern business, which is one of the business sectors in the beverage procurement sector, is a low-risk business, so business licensing is only limited to Business Identification numbers (NIB). Furthermore, regulations related to the requirements for business permits for Beverage Shops with the enactment of PP Number 5 of 2021 revoke the previous regulations regarding the implementation of business licensing services, namely PP No. 24 of 2018regarding Electronically Integrated Business Licensing Services. In this research, it is hoped that the Central Government will establish regulations that specifically function as filtering the tourism sector business, especially the tavern business sector so that the classification of business sectors by sector is in line with the Indonesian Business Field Standard Classification, which is compiled for statistical purposes and establishes business activity standards that apply to businesses with a low level of risk so that they can become rules that can be used as the basis for supervision of the implementation of business licensing.